Cover Picture: Smartphone‐coupled Electrochemical Analysis of Cellular Superoxide Anions Based on Mnx(PO4)y Monolayer Modified Porous Carbon (Electroanalysis 3/2020). Issue 3 (4th March 2020) - Cai, Xuan; Gao, Qianmei; Zuo, Shaohua; Zhao, Hongli; Lan, Minbo
Abstract : The cover picture shows a palm‐sized electrochemical sensor for the determination of cell‐released superoxide anions based on a self‐developed potentiostat, which can be connected with both smartphones and computers. Nanomaterial based on Mnx (PO4 )y layer modified porous carbon cubic was synthesized and used as functional material on the surface of working electrode. The palmsized‐sensor was demonstrated to exhibit satisfying performance for real‐time monitoring of superoxide anions released from cancer cells. More Details can be found in the article by Xuan Cai, Qianmei Gao, Shaohua Zuo, Hongli Zhao, and Minbo Lan, DOI: 10.1002/elan.201900623.